Spatially localized 1H NMR spectra of metabolites in the human brain. - Hanstock, C C (1988)
Using a surface coil, we have obtained 1H NMR spectra from metabolites in the human brain. Localization was achieved by combining depth pulses with image-selected in vivo spectroscopy magnetic field gradient methods. 1H spectra in which total creatine (3.03 ppm) has a signal/noise ratio of 95:1 were obtained in 4 min from 14 ml of brain. A resonance at 2.02 ppm consisting predominantly of N-acetylaspartate was measured relative to the creatine peak in gray and white matter, and the ratio was lower in the white matter. The spin-spin relaxation times of N-acetylaspartate and creatine were measured in white and gray matter and while creatine relaxation times were the same in both, the N-acetylaspartate relaxation time was longer in white matter. Lactate was detected in the normoxic brain and the average of three measurements was approximately equal to 0.5 mM from comparison with the creatine plus phosphocreatine peak, which was assumed to be 10.5 mM.